2018
DOI: 10.1016/j.bbadis.2018.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Acidic pHe regulates cytoskeletal dynamics through conformational integrin β1 activation and promotes membrane protrusion

Abstract: An acidic extracellular pH (pHe) in the tumor microenvironment has been suggested to facilitate tumor growth and metastasis. However, the molecular mechanisms by which tumor cells sense acidic signal to induce a transition to an aggressive phenotype remain elusive. Here, we showed that an acidic pHe (pH 6.5) stimulation resulted in protrusion and epithelial-mesenchymal transition (EMT) of cancer cells, which promoted migration and matrix degeneration. Using computational molecular dynamics simulations, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…The fact that the acidic pH microenvironment induces tumor growth is an accepted fact. It is notable that cell signaling cascades in cancer cells, in part, are different from those in nonmalignant cells (LaMonte et al, 2013;Li et al, 2018). Knowing the true cellular signaling pathways in cancer cells contributes to finding more effective treatments.…”
Section: Autophagy Measurement Using Ao Stainingmentioning
confidence: 99%
“…The fact that the acidic pH microenvironment induces tumor growth is an accepted fact. It is notable that cell signaling cascades in cancer cells, in part, are different from those in nonmalignant cells (LaMonte et al, 2013;Li et al, 2018). Knowing the true cellular signaling pathways in cancer cells contributes to finding more effective treatments.…”
Section: Autophagy Measurement Using Ao Stainingmentioning
confidence: 99%
“…During this stage, the F-actin and the lamellipodium are the two crucial media linking the cellular behaviors and the mechanical properties. It has been reported that the acid extracellular pH induces the reorganization of F-actin cytoskeleton and facilitates the formation of lamellipodial protrusion [25], which can modulate the morphology and rigidity against the forces needed for cell migration [47]. It would be a key challenge and a great significance to study the correlation between the organization of F-actin structures and the viscoelasticity distribution in lamellipodium of living cancer cells under normal (pH 7.4) and acid (pH 6.5) microenvironments for revealing the nanomechanical mechanism of the cellular migration in metastasis.…”
Section: Topography and Viscoelasticity Of Cytoskeletons In Lamellipodium At Ph 74mentioning
confidence: 99%
“…The malignant degree of cancer cells is related to their migration speed, that is, the metastasis and invasiveness of cancer cells [21]. In particular, in the complex microenvironment of tumor tissues [22,23], the cancer cells will change the structure and topography of lamellipodia at an acid pH level, and then accelerate their metastasis [24,25]. However, the organization of the F-actin in lamellipodia under different pH microenvironments associated with the underlying relationship with the viscoelasticity and migration of living cancer cells remain unclear and is in urgent need to be fully interpreted.…”
Section: Introductionmentioning
confidence: 99%
“…pH is a matrix property essential for invadopodium formation. Integrins mediate cellular cues and can act as pH sensors to regulate actin protrusions [206]. α5β1, αIIβ3 and αVβ3 modify their structural activation depending on pH, and acidic stimulation promotes integrin headpiece opening and FAK-SRC signaling induction [206].…”
Section: Microenvironment Factors Associated With Invadosome Formamentioning
confidence: 99%
“…Integrins mediate cellular cues and can act as pH sensors to regulate actin protrusions [206]. α5β1, αIIβ3 and αVβ3 modify their structural activation depending on pH, and acidic stimulation promotes integrin headpiece opening and FAK-SRC signaling induction [206]. During invadopodium maturation, cortactin phosphorylation recruits Na + /H + exchanger-1 (NHE1) to increase intracellular pH, which releases cofilin from cortactin molecules during invadopodium elongation [207].…”
Section: Microenvironment Factors Associated With Invadosome Formamentioning
confidence: 99%